Disaggregated crude oil prices and stock market behaviour in Nigeria: Evidence from sectorial analysis - Titus Ojeyinka; Anthonia Emoshokemhe Aliemhe (Universitas Islam Indonesia, 2023)
Purpose ― This study differs from previous studies by examining the impact of oil price components, namely oil demand, global oil supply, and oil market-specific demand, on the stock returns of five sectors (Banking, Consumer goods, Industrial, Insurance, and Oil and Gas) listed on the Nigerian Stock Exchange. Design/Method/Approach ― The study employs the Autoregressive Distributed Lag (ARDL) model on monthly data between January 2000 and December 2019. Findings ― The paper finds evidence of a long-run relationship between sectoral market returns and oil price changes in Nigeria. Further evidence from the study reveals that oil-specific demand and global oil demand have positive and significant effects on the aggregate stock returns and the returns of the sampled sectors. On the other hand, the impact of the global oil supply is inconsequential on the aggregate stock returns and sectoral returns except for the Oil and Gas sector, where the effect of global oil production is positive and significant. Implication ― The study concludes that stock market returns in Nigeria are sensitive and vulnerable to changes in demand-side components of oil price. The study also highlights important policy implications to enhance the performance of the Nigerian stock market. Originality/Value ― The paper examines the impact of disaggregated oil prices on sectoral returns of the five listed sectors on the Nigerian Stock Exchange, which has not been explored in the literature.